ANALISIS PERSEPSI PELAJAR SEKOLAH MENENGAH ATAS TERHADAP PERKEMBANGAN TEKNOLOGI ARTIFICIAL INTELLIGENCE (AI) DALAM PEMBELAJARAN BAHASA - Hermawan, Dimas (Universitas Tanjungpura, 2024)
Education is a field that often undergoes transformation in line with developments over time, technology and societal demands. One of the latest breakthroughs that is in the spotlight in the education sector is the use of Artificial Intelligence (AI). This research aims to analyze high school students